Education and learning to support a just transition in Central Appalachia - Colleen Unroe (Adult Education Research Conference, 2020)
This case study explores the learning and education of a community organization involved with multiple Just Transition initiatives in Eastern Kentucky where the economies were formerly dominated by the coal industry. Sixteen semi-structured interviews were conducted of leaders within the organization in addition to exploring the educational materials. Although non-formal learning plays an important part, informal learning, activist exchanges, and communities of practice play a more fundamental role in the activist learning.
Keywords: Just Transition; social movement learning; informal learning; communities of practice; non-formal learning; Appalachia